The occurrence of Ixodes ricinus ticks and important tick-borne pathogens in areas with high tick-borne encephalitis prevalence in different altitudinal levels of the Czech Republic Part II. Ixodes ricinus ticks and genospecies of Borrelia burgdorferi sensu lato complex - Daniel, M; Rudenko, N; Golovchenko, M; Danielová, V; Fialová, A; Kříž, B; Malý, M (Epidemiologie, mikrobiologie, imunologie, 2016)
STUDY OBJECTIVE: Three years long research study (2011-2013) on population density of Ixodes ricinus and the infection rate of the pathogens that they transmit was conducted in four topographically distant areas in the Czech Republic. In the previous decade (2001-2010) thirteen loci with increased incidence of tick borne encephalitis cases were defined, suggesting the permanent interaction of human population with ticks and indicating the landmarks for study of the presence of other tick borne pathogens. The work program included the identification of existing spectrum of spirochetes from Borrelia burgdorferi sensu lato complex and the conditions of their occurrence and distribution. MATERIAL AND METHODS: In the areas of the Ústí nad Labem Region, Olomouc Region, South Bohemian Region, and Highlands Region, 600 m2 plots were selected in the local optimal I. ricinus habitats where tick flagging was performed every year in the spring-summer and autumn seasons of the tick questing activity. Collected adult ticks (1369 males and 1404 females) were individually screened for B. burgdorferi s. l. spirochets. RESULTS: Spirochetes from B. burgdorferi s.l. complex were detected in all 13 studies sites in all altitudes from 280 to 1030 meters a. s. l. The total rate of infection was determined as 11.4% (males 10.4%, females 12.4%) with range limits from 1.4% (Ústí nad Labem in 2011) to 19.7% (South Bohemian Region, 2012).Genospecies were detected in various proportions and in different combinations: Borrelia afzelii, B. garinii, B. burgdorferi s. s., B. bavariensis, B. bissettii, B. valaisiana, B. spielmanii and B. lusitaniae. The three-year observation justifies the assumption that the regional differences in infectivity of I. ricinus are based on the character of the local biocenosis of the respective region. The dynamics of its seasonal changes, conditioned by climatic factors, determines the annual differences. CONCLUSION: Three of the medically most important Borrelia species formed a core group among all detected genospecies. B. afzelii was a dominated one (115 detections), followed by B. garinii (100) and by B. burgdorferi s.s. (19). Other genospecies were detected sporadically. However, the detection of B. bissettii should be emphasized due to the recently proven pathogenic effects of this genospecies and yet little-known sporadic expansion in the Czech Republic. The medical importance and distribution of other sporadically occurred genospecies is also discussed.Key words: Ixodes ricinus - Borrelia afzelii - B. garinii - B. burgdorferi s. s. - B. bavariensis - B. valaisiana - B. spielmanii - B. lusitaniae - B. bissettii - distribution - altitude - season - medical importance.
Keywords: Prevalence; Česká republika; Ixodes; Encephalitis, Tick-Borne; Czech Republic; Borrelia burgdorferi; prevalence; Male; klíště; Animals; lidé; Female; mužské pohlaví; ženské pohlaví; Humans; zvířata; klíšťová encefalitida